1990
DOI: 10.1002/anie.199003441
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Oxides: Zwitterions or Diradicals?

Abstract: Over the last few years new experimental and theoretical methods have made it possible to gain a more detailed insight into the chemistry of short-lived reaction intermediates. In 1949 Criegee postulated the intermediacy of carbonyl oxides in the mechanism of ozonolysis, and since then these species have become the goal of much research effort. Even though the formation of "Criegee zwitterions" during ozonolysis and carbene oxidations was proven by scavenger experiments, the electronic structure -zwitterion or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(139 citation statements)
references
References 97 publications
10
126
0
3
Order By: Relevance
“…diradicals) in the literature on the heterogeneous ozonolysis of OL. The discord in this description has its roots in part in the debate on the electronic structure of these intermediates that are extant in the organic chemistry literature (Bunnelle, 1991;Harding and Goddard III, 1978;Sander, 1990). Criegee showed that for ozonolysis in solutions there was evidence indicating CI were zwitterionic (Criegee, 1975) based on reactivity trends (Criegee, 1975;Criegee and Wenner, 1949).…”
Section: Overview Of Ozonolysismentioning
confidence: 99%
See 1 more Smart Citation
“…diradicals) in the literature on the heterogeneous ozonolysis of OL. The discord in this description has its roots in part in the debate on the electronic structure of these intermediates that are extant in the organic chemistry literature (Bunnelle, 1991;Harding and Goddard III, 1978;Sander, 1990). Criegee showed that for ozonolysis in solutions there was evidence indicating CI were zwitterionic (Criegee, 1975) based on reactivity trends (Criegee, 1975;Criegee and Wenner, 1949).…”
Section: Overview Of Ozonolysismentioning
confidence: 99%
“…In this section we will present a concise summary of the established reactivity of CI for these cases and in the following sections provide discussion that the CI react more in accord with solution chemistry. We will not present any details regarding a third experimental regime, namely investigations of CI in inert matrices under cryogenic conditions but interested readers can find several reviews (Bunnelle, 1991;Sander, 1990) that cover this topic of extensive research.…”
Section: Overview Of Ozonolysismentioning
confidence: 99%
“…1 The important roles of reactive species of this type, commonly known as Criegee intermediates, are generally accepted in ozonolysis reactions in organic chemistry and atmospheric chemistry, [2][3][4][5][6][7] even though these intermediates have not been detected directly in the gaseous phase until recently. The reactions of ozone with alkenes are important in the atmosphere because they are responsible for the non-photolytic production of OH, an important oxidizing and cleansing agent in the atmosphere, especially under conditions of dim light such as during winter and at night.…”
Section: Introductionmentioning
confidence: 99%
“…Os exemplos 7 e 8 indicam que óxidos carbonílicos, gerados in situ por fotooxigenação dos correspondentes diazoalcanos [10][11][12] , são oxidantes nucleofílicos. Os exemplos 9-10 e 11-12 apenas confirmam que oxidantes nucleofílicos apresentam X SO próximo de 1,0, e para oxidantes eletrofílicos X SO próximo de zero, respectivamente.…”
Section: Figuraunclassified
“…Cálculos teóricos [5][6][7][8][9] e dados espectroscópicos [10][11][12][13][14][15] estabeleceram inequivocadamente que dioxiranos 1 e óxidos carbonílicos 2 são espécies isoméricas separadas por uma elevada barreira energética. Bach e colaboradores 6,7 , através de cálculos ab initio, encontraram para a interconversão do dioxirano 1a (R 1 = R 2 = H) no respectivo óxido carbonílico 2a uma barreira energética na faixa de 29,7 a 54,1 kcal.mol -1 .…”
unclassified